Examples

x2-3x=0
Step 1
Factor x out of x2-3x.
Tap for more steps...
Step 1.1
Factor x out of x2.
xx-3x=0
Step 1.2
Factor x out of -3x.
xx+x-3=0
Step 1.3
Factor x out of xx+x-3.
x(x-3)=0
x(x-3)=0
Step 2
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
x=0
x-3=0
Step 3
Set x equal to 0.
x=0
Step 4
Set x-3 equal to 0 and solve for x.
Tap for more steps...
Step 4.1
Set x-3 equal to 0.
x-3=0
Step 4.2
Add 3 to both sides of the equation.
x=3
x=3
Step 5
The final solution is all the values that make x(x-3)=0 true.
x=0,3
Enter YOUR Problem
Mathway requires javascript and a modern browser.
 [x2  12  π  xdx ] 
AmazonPay